Evaluasi Penerapan Proteksi Radiasi pada Ruangan dan Pekerja Radiasi di Instalasi Radiologi Rumah Sakit Universitas Andalas - Rahmawati, Indy; Milvita, Dian; Hiswara, Eri (Universitas Andalas, 2025)
Research has been carried out regarding the evaluation of the application of radiation protection to rooms and radiation workers in the Radiology Installation at Andalas University Hospital. The aim of the research is to evaluate the radiation dose rate on the inside and outside walls of the room, evaluate the radiation dose rate received by radiation workers, and evaluate the completeness of the work area and radiation protection for radiation workers. Evaluation of the radiation dose rate on the radiation shield wall was carried out using the TLD-100 in the CT-Scan, conventional X-ray and dental rooms. Evaluation of the radiation dose rate received by radiation workers is carried out using the TLD badge worn by radiation workers. Evaluation of the completeness of the work area is carried out by directly observing the radiology room, then conducting interviews with radiation workers. The research results showed that the highest radiation dose rate was obtained in the CT-Scan room and the lowest was outside the dental room at the entrance, without exceeding the Dose Limit Value (NBD) set by BAPETEN Regulation No. 4 of 2013 of 20 mSv/year for radiation workers and 1 mSv/year for the general public. The radiation dose rate value received by radiation workers is still below the NBD set by BAPETEN Regulation No. 4 of 2013 amounting to 20 mSv/year. The results of the evaluation of the completeness of the work area and radiation protection in general have met the provisions of BAPETEN Regulation No. 4 of 2020 except for danger signs in conventional X-ray and CT-Scan rooms.